The Efficacy of a Computer-Assisted Cognitive Rehabilitation Program for Patients with Mild Cognitive Deficits: A Pilot Study. Issue 1 (1st January 2017) - Mansbach, William E.; Mace, Ryan A.; Clark, Kristen M.
Abstract : Background/Study Context: Whereas computer-assisted cognitive rehabilitation (CR) programs show promise as tools for improving cognition in certain populations, there is not a consensus regarding their efficacy. This study focuses on restorative CR, a treatment designed to improve cognitive functioning affected by progressive brain changes due to disease or aging, through computer-assisted cognitive exercises. The purpose of this study was to investigate the efficacy of a computer-assisted restorative CR intervention for improving cognitive functioning in older rehabilitation patients with relatively mild cognitive deficits . Methods: Older adult residents in a Maryland retirement community ( N  = 43) who met inclusion criteria were assigned to either the CR treatment or the control group. Treatment group participants completed 3 weeks (nine sessions) of Memory Match, an online CR module designed to improve attention and visual memory, whereas the control group did not complete the CR program after the baseline assessment. Analyses were based on the 38 ( n  = 20 treatment, n =  18 control) participants (mean age = 78.08 ± 10.31) who completed the post-assessment Brief Cognitive Assessment Tool (BCAT) and a self-rating inventory (SRI) of cognitive ability . Results: Treatment group participants who received the CR treatment obtained significantly higher BCAT scores (medium to large effect size) at post-assessment than control group participants over the same period. Additional evidence for the efficacy of the CR program was found by comparing responses on a SRI of cognitive ability between the two groups . Conclusion: The authors discuss the merits and shortcoming of this pilot study, the utility of the CR program for older rehabilitation patients with relatively mild cognitive deficits, and ideas for future research .